Our #1 Challenge: Retirement Insecurity. Issue 4 (1st September 2018) - Ellis, Charles D.
Abstract : One of the consequences of the shift in corporate retirement plans from defined benefit to defined contribution is widespread retirement insecurity. Although most people in the top one-third of economic affluence will be fine, for the other two-thirds—particularly the bottom one-third—the problem is a serious threat. We can prevent this painful future if we act sensibly and soon by raising the alarm with our corporate and government leaders.